Fucoidan-Based Gold Nanoparticles: Antioxidant and Anticancer Potential from Turbinaria decurrens and Sargassum cinereum - Ahmed S. El Newehy; Saly F. Gheda; Mona M. Ismail; Dara Aldisi; Mahmoud M. A. Abulmeaty; Mostafa E. Elshobary (Pharmaceutics, 2025)
Background/Objectives: Cancer remains one of the leading causes of mortality worldwide, while natural antioxidants have emerged as promising therapeutic agents in cancer treatment. Although fucoidan from brown algae shows anticancer potential, its efficacy is limited by bioavailability challenges, and the synergistic effects of combining it with gold nanoparticles remain unexplored. Methods: Fucoidan was extracted from Sargassum cinereum and Turbinaria decurrens. F-AuNPs were produced utilizing fucoidan as both a reducing and stabilizing agent. The nanoparticles were analyzed by UV-Vis spectroscopy, FTIR, TEM, XRD, DLS, TAG, and zeta potential evaluation. The antioxidant activity was evaluated by DPPH and FRAP tests. Cytotoxicity was determined against HepG2, THP-1, and BNL cells, utilizing MTT and SRB tests. Flow cytometry was utilized to assess the cell cycle, while molecular docking was carried out to examine binding to oncogenic proteins. Results: T. decurrens produced higher polysaccharides rich in fucoidan content (235.9 mg/g dry weight) and stated higher antioxidant activity (FRAP: 9.21 μg TE mg−1; DPPH: 4.48 μg TE mg−1) in comparison to S. cinereum. F-AuNPs showed potent cytotoxicity toward HepG2 cells, with IC50 values and cytotoxicity toward HepG2 cells, with IC50 values of 377.6 μg/mL for S. cinereum and 449.5 μg mL−1 for T. decurrens. Molecular docking revealed robust binding of fucoidan to COX-2 (−7.1 kcal mol−1) and TERT (−5.4 kcal mol−1). Conclusions: Fucoidan and F-AuNPs reveal remarkable antioxidant and anticancer properties. Nanoparticle formulation greatly improves bioactivity, underscoring its promise as a synergistic approach for cancer treatment by influencing oxidative stress and cancer-associated pathways.